Smart grid test bed using OPNET and power line communication - Huh, Jun-Ho (IGI Global, 2018)
Presents an innovative perspective on the design, development, and implementation of an expandable test bed for smart grid applications. Highlighting pertinent topics such as intrusion detection, user interface, and performance evaluation, this book is an ideal reference source for researchers, academics, engineers, students, and professionals interested in smart grid technologies.